2020
DOI: 10.1099/ijsem.0.003914
|View full text |Cite
|
Sign up to set email alerts
|

Seongchinamella unica gen. nov., sp. nov., isolated from a tidal mudflat of beach, and transfer of Halioglobus sediminis to Seongchinamella sediminis comb. nov. and Halioglobus lutimaris to Pseudohalioglobus gen. nov. as Pseudohalioglobus lutimaris comb. nov.

Abstract: The DDBJ/ENA/GenBank accession numbers for 16S rRNA gene and genome sequences of strain GH4-78 T are MG905440 and SMSE00000000, respectively. The version of the genome sequence described in this paper is version SMSE01000000. Three supplementary figures and three supplementary tables are available with the online version of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 30 publications
(51 reference statements)
1
7
0
Order By: Relevance
“…S4) showed that strain HB171799 T formed a distinct subbranch within the family Oceanospirillaceae and related taxa, and was clearly separated from members of the genera Marinomonas and Nitrincola, which were the closest associated taxa based on 16S rRNA gene sequence comparison. This result supported that strain HB171799 T [32,33]. On the basis of the AAI, dDDH and ANI values between HB171799 T and the most closely members of genera Marinomonas and Nitrincola, HB171799 T could be classified within a novel genus, although the POCP values are higher than the threshold value of 50 % [28].…”
Section: Genome Featuressupporting
confidence: 68%
See 1 more Smart Citation
“…S4) showed that strain HB171799 T formed a distinct subbranch within the family Oceanospirillaceae and related taxa, and was clearly separated from members of the genera Marinomonas and Nitrincola, which were the closest associated taxa based on 16S rRNA gene sequence comparison. This result supported that strain HB171799 T [32,33]. On the basis of the AAI, dDDH and ANI values between HB171799 T and the most closely members of genera Marinomonas and Nitrincola, HB171799 T could be classified within a novel genus, although the POCP values are higher than the threshold value of 50 % [28].…”
Section: Genome Featuressupporting
confidence: 68%
“…Strain HB171799 T exhibited the ANI, dDDH (the recommended results from formula 2), AAI and POCP values of 66.9–73.4 %, 19.8–25.3 %, 51.6–71.7 % and 40.1–68.8 % with the four related taxa, respectively (Table S2), which were strikingly lower than the threshold values of the species boundary (ANI 94–96 %, dDDH 70 %, and AAI 95–96 %) [24, 30, 31]. It was recently shown that a pairwise ANI of 74.5–75.5 % and AAI ≤74 % can be used for assignment of a new genus in the family Oceanospirillaceae [32, 33]. On the basis of the AAI, dDDH and ANI values between HB171799 T and the most closely members of genera Marinomonas and Nitrincola , HB171799 T could be classified within a novel genus, although the POCP values are higher than the threshold value of 50 % [28].…”
Section: Genome Featuresmentioning
confidence: 99%
“…Pairwise ANI values between strain C5-26 T and its closest phylogenetic neighbours were 74.17 % with L. halotolerans C296001 T , 73.56 % with L. mongoliensis NBRC 105296 T and 72.62 % with B. hedensis DSM 22951 T , well below the recommended threshold of 95-96 % for species delineation[30]. Moreover, it was recently shown that a pairwise ANI of 74.50-75.50 % can be used for assignment of a new genus in the Gammaproteoacteria[31].…”
mentioning
confidence: 93%
“…The family Halieaceae proposed by Spring et al [1], previously known as the OM60/NOR5 clade of the oligotrophic marine Gammaproteobacteria group [2], belongs to the order Cellvibrionales , class Gammaproteobacteria . The family Halieaceae includes 12 genera (https://lpsn.dsmz.de/family/halieaceae) at the time of writing, Haliea [3], Congregibacter [4], Chromatocurvus [5, 6], Halioglobus [7, 8], Luminiphilus [6], Pseudohaliea [6, 9], Parahaliea [10–12], Marimicrobium [13], Kineobactrum [14], Pseudohalioglobus [15, 16], Seongchinamella [15, 17] and ‘ Aequoribacter ’ (Li SH et al ., 2020 [18]). Most of them were isolated from marine environments, such as seawater, marine sediment, brine spring and tidal mudflat.…”
Section: Introductionmentioning
confidence: 99%
“…dsmz. de/ family/ halieaceae) at the time of writing, Haliea [3], Congregibacter [4], Chromatocurvus [5,6], Halioglobus [7,8], Luminiphilus [6], Pseudohaliea [6,9], Parahaliea [10][11][12], Marimicrobium [13], Kineobactrum [14], Pseudohalioglobus [15,16], Seongchinamella [15,17] and 'Aequoribacter' (Li SH et al, 2020 [18]). Most of them were isolated from marine environments, such as seawater, marine sediment, brine spring and tidal mudflat.…”
Section: Introductionmentioning
confidence: 99%